Development of a strategic tool for shared decision-making in the use of antidepressants among patients with major depressive disorder: A focus group study - Zaini, Syahrir; Bharathy, Harvin Anbu Manivanna; Sulaiman, Ahmad Hatim; Gill, Jesjeetsingh; Hui, Koh Ong; Zaman Huri, Hasniza; Guan, Ng Chong (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
Shared decision-making (SDM) has been recognized as an important tool in the mental health field and considered as a crucial component of patient-centered care. Therefore, the purpose of this study was to develop a strategic tool towards the promotion and implementation of SDM in the use of antidepressants among patients with major depressive disorder. Nineteen doctors and 11 major depressive disorder patients who are involved in psychiatric outpatient clinic appointments were purposively selected and recruited to participate in one of six focus groups in a large teaching hospital in Malaysia. Focus groups were transcribed verbatim and analyzed using a thematic approach to identify current views on providing information needed for SDM practice towards its implementation in near future. Patients’ and doctors’ views were organized into six major themes, which are; summary of treatment options, correct ways of taking medication, potential side effects of treatments related to patients, sharing of case study related to the treatment options, cost of treatment options, and input from pharmacist. The information may be included in the SDM tool which can be useful to inform further research efforts and developments that contribute towards the successful implementation of SDM into clinical practice.